Meningkatkan Keaktifan Siswa melalui Proyek Kewarganegaraan Antikorupsi di SMK Pawyatan Daha 2 Kediri - Idang Ramadhan; Yunita Kusumaningrum; Hanik Tri Wilujeng (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study was motivated by the low student activeness at Pawyatan Daha 2 Kediri Vocational High School (SMK), Kediri City. This research is included in the Kemmis & McTaggart model of classroom action research through a civic project containing anti-corruption material. The subjects of this study were students of class XII Office Automation and Governance (OTKP) 1 totaling 35 students consisting of 1 male student and 34 female students. The sample selection was carried out by saturation sampling, where all members of the population were sampled in the study. Data in this study were collected using observation, questionnaire, and documentation techniques. Data analysis used in this research is a descriptive analysis technique with percentages. The results of this study indicate that the implementation of anti-corruption citizenship projects can increase the activeness of class XII students of Office Automation and Governance (OTKP) 1 at SMK Pawyatan Daha 2 Kediri in the odd semester of the 2022/2023 academic year, this is seen through five aspects, namely paying attention to lessons, cooperation, and social interaction, submitting proposals/ideas, problem-solving, discipline. The aspects that increased significantly were paying attention to lessons and discipline. In addition, this study shows that harmonizing learning methods, material characteristics, and learner characteristics is essential in preparing lesson plans that can increase student activeness.